Echo's Chambers : Architecture and the Idea of Acoustic Space - Clarke, Joseph L. (Book collections on Project MUSE., 2021)
A room's acoustic character seems at once the most technical and the most mystical of concerns. Since the early Enlightenment, European architects have systematically endeavored to represent and control the propagation of sound in large interior spaces. Their work has been informed by the science of sound but has also been entangled with debates on style, visualization techniques, performance practices, and the expansion of the listening public. Echo's Chambers explores how architectural experimentation from the seventeenth through the mid-twentieth centuries laid the groundwork for concepts of acoustic space that are widely embraced in contemporary culture. It focuses on the role of echo and reverberation in the architecture of Pierre Patte, Claude-Nicolas Ledoux, Carl Ferdinand Langhans, and Le Corbusier, as well as the influential acoustic ideas of Athanasius Kircher, Richard Wagner, and Marshall McLuhan. Drawing on interdisciplinary theories of media and auditory culture, Joseph L. Clarke reveals how architecture has impacted the ways we continue to listen to, talk about, and creatively manipulate sound in the physical environment.